Activity-Based Probes to Utilize the Proteolytic Activity of Cathepsin G in Biological Samples - Burster, Timo; Gärtner, Fabian; Knippschild, Uwe; Zhanapiya, Anuar (Frontiers in Chemistry, 2021)
Neutrophils, migrating to the site of infection, are able to release serine proteases after being activated. These serine proteases comprise cathepsin G (CatG), neutrophil elastase (NE), protease 3 (PR3), and neutrophil serine protease 4 (NSP4). A disadvantage of uncontrolled proteolytic activity of proteases is the outcome of various human diseases, including cardiovascular diseases, thrombosis, and autoimmunity. Activity-based probes (ABPs) are used to determine the proteolytic activity of proteases, containing a set of three essential elements: Warhead, recognition sequence, and the reporter tag for detection of the covalent enzyme-activity-based-probe-complex. Here we will summarize the latest findings of ABP-mediated detection of proteases in both locations intracellularly and on the cell surface of cells, thereby focusing on CatG. Particularly, application of ABPs in regular flow cytometry, imaging flow cytometry, and mass cytometry by time-of-flight (CyTOF) approaches is advantageous when distinguishing between immune cell subsets. ABPs can be included in a vast panel of markers to detect proteolytic activity and determine whether proteases are properly regulated during medication. The use of ABPs as a detection tool opens the possibility to interfere with uncontrolled proteolytic activity of proteases by employing protease inhibitors.